Implementasi Strategi Guru PAI dalam Meningkatkan Minat Belajar Siswa Kelas X di SMAN 1 Mojotengah - Puput Anjarwati; Maryono; Fatiatun (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study aims to describe the implementation of Islamic Religious Education (PAI) teachers' strategies in enhancing the learning interest of tenth-grade students at SMA Negeri 1 Mojotengah, identify the challenges encountered during their implementation, and examine the efforts made to overcome these challenges. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings revealed that PAI teachers implemented active, contextual, and collaborative learning strategies through group discussions, question-and-answer sessions, presentations, and problem-solving activities related to students’ daily lives. These strategies contributed to increased attention, engagement, enthusiasm, and participation among students during the learning process. The challenges encountered included low learning motivation among some students, differences in learning abilities and characteristics, limited instructional time, excessive mobile phone use, and the suboptimal utilization of learning media. To address these challenges, teachers employed more varied instructional methods, continuously provided motivation, adopted personal approaches to students, utilized diverse learning resources, and collaborated with parents. The study concludes that appropriate instructional strategies, supported by engaging learning media, play a significant role in fostering students’ interest in learning Islamic Religious Education.